Penerapan Model Pembelajaran Peningkatan Kemampuan Berpikir Terhadap Hasil Belajar Siswa Kelas IV pada Mata Pelajaran IPS - Seven Rianto Gulo; Indah Wijaya Lase; Dios Tebendiga Gulo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims (1) to find out the Application of the Learning Model to Improve Thinking Ability in the teaching and learning process in social studies class IV at SD Negeri 071082 Lawelu in the 2022/2023 academic year, (2) to find out student learning outcomes in social studies through Learning Application Model for Increasing Thinking Ability. The method used to obtain research data was the Classroom Action Research method with 16 class IV students as research subjects. The research instruments used in this study were teacher observation sheets, student observation sheets, learning achievement tests and documentation. have been carried out, namely (1) the average results of the teacher observation sheet in the first cycle were 61.1596 in the sufficient category and in the second cycle it increased to 88.4224 in the very good category. (2) The average proportion of student observation sheets in the first cycle was 54.6826 which was considered sufficient and in the second cycle it increased to 87.192 which was classified as very good. (3) The average student learning outcomes in cycle I was 71.03 with a completeness proportion of 66.6790 which was quite sufficient, while in cycle II the average student learning score was 83.45 with a completeness proportion of 95.8420. The researcher concluded that there was an increase in learning outcomes in social studies subjects in grade IV through the application of the Thinking Ability Improvement Learning Model at SD Negeri 071082 Lawelu in the 2022/2023 academic year. Keywords: Learning Model to Improve Thinking Ability, Social studies, Learning Outcomes